Bone Mineral Density Loss in Parkinson's Disease: Impact of Clinical Subtypes. Issue 4 (8th August 2021) - Özcan, Hakan; Acaröz Candan, Sevim; Gül, Tuba
ABSTRACT: Background : This study aimed to compare the BMD status among the clinical subtypes of PD and healthy controls. Methods : Sixty patients with PD and 30 healthy age- and sex-matched controls were included in this study. The patients were divided into postural instability gait difficulty-dominant type (PIGDDT) group and tremor-dominant type (TDT) group based on the Unified Parkinson's Disease Rating Scale (UPDRS) score. BMD was measured using dual-energy X-ray absorptiometry scans in femoral and lumbar regions. Results : The T-scores in femoral and lumbar regions were similar in all groups. The prevalence of osteopenia was higher than the prevalence of osteoporosis in all three groups for femoral regions. The prevalence of osteoporosis in the intertrochanteric region and total femur in the PIGDDT group was higher than in the TDT group and controls. Our data showed a trend toward higher prevalence of osteoporosis in the PIGDDT group. Conclusion : The prevalence of osteopenia and osteoporosis may differ between clinical subtypes of PD and healthy controls. Osteopenia is more common than osteoporosis for all groups. The patients with PIGDDT of PD tended to have higher prevalence of osteoporosis, even at early stages of disease, compared to those with TDT and healthy controls.